Expression cloning of a rat brain somatostatin receptor cDNA. - Kluxen, F W (1992)
We have used an expression-cloning strategy to isolate a cDNA encoding a somatostatin (somatotropin release-inhibiting factor, SRIF) receptor from rat cortex and hippocampus. A positive clone was identified by autoradiography after binding of radiolabeled SRIF to COS-1 cells previously transfected with pools of cDNA clones. The deduced amino acid sequence of the receptor displays sequence and structural homology to the family of G-protein-coupled receptors. The affinity of various SRIF analogs to the expressed receptor resembles their effects on growth hormone release from pituitary cells. In addition, the distribution of the mRNA in various tissues corresponds to that described for native SRIF receptors. Therefore, we conclude that we have isolated a rat brain SRIF receptor cDNA.